Additionally sulfated xylomannan sulfates from Scinaia hatei and their antiviral activities - Ray, Sayani (2015)
Herpes simplex viruses (HSVs) display affinity for cell-surface heparan sulfate proteoglycans with biological relevance in virus entry. This study demonstrates the potential of chemically engineered sulfated xylomannans from Scinaia hatei as antiHSV drug candidate. Particularly, a dimethylformamide -SO3/pyridine based procedure has been employed for the generation of anionic polysaccharides. This one-step procedure has the power of providing a spectrum of xylomannans with varying molecular masses (<12-74 kDa), sulfate content (1-50%) and glycosyl composition. Especially, the sulfated xylomannans S1F1 and S2F1 possessed altered activity against HSV-1 and HSV-2 compared to the parental compound (F1) and that too in the absence of drug-induced cytotoxicity. Regarding methodological facet, the directive decoration of hydroxyl functionality with sulfate group plus changes in the molecular mass and sugar composition during isolation by the used reagent opens a door for the production of new molecular entity with altered biological activity from other natural sources.